Terapi Psikoedukasi Terhadap Tingkat Kecemasan Pasien Kemoterapi Kanker Payudara - Sumarni Sumarni; Afiyah Sri Harnany; Hartati Hartati; Tri Anonim (Prodi Keperawatan Purwokerto, 2018)
Ca mamae or breast cancer is the most common malignant disease in women.Based on the data obtained from the Medical Record section of the Kraton Hospital in Pekalongan Regency in 2016 there were 1.37% of patients in the count number of patients with breast cancer. The number of breast cancer patients in January 2018 was 96 patients, this number increased compared to the month December 2017 as many as 62 patients. One of the management of breast cancer that can be done is by chemotherapy. Breast cancer and its handling besides giving physical impact but also psychological impact on the sufferer. The psychological impact includes feelings of anxiety. Anxious circumstances that are too often experienced result in not good, because it will affect the patient's immune system, so that cancer patients need an intervention to reduce anxiety, one of them is to obtain adequate information, through psychoeducation therapy.The aim of the study was to determine the effect of psychoeducation on the level of anxiety in breast cancer chemotherapy patients. The type of research used was quasi experiment with pre test - post test without control research design. The study population was breast cancer patients who would undergo chemotherapy in Kraton Hospital Pekalongan Regency. Study sample of breast cancer patients who will undergo chemotherapy. Sampling technique with consecutive sampling with a sample size of 20 respondents.The instruments used were anxiety level measurement sheets. The results of the study obtained 55% of respondents aged 50 years, 35% of respondents had a family history of breast cancer, There were significant differences in the average anxiety before psychoeducation with after psychoeducation with p = 0,000, so the conclusion there is a significant influence of psychoeducation against anxiety in breast cancer patients undergoing chemotherapy